Expert Recommendations Based on Opinion Mining of User‐Generated Product Reviews. (25th October 2013) - Stavrianou, Anna; Brun, Caroline
<x xml:space="preserve">Abstract</x> In this article, we introduce the idea of expert recommendations whose objective is to relate review comments with users' tasks or expectations. We propose to use fine‐grained information such as opinions and suggestions extracted using natural language processing techniques from user reviews about products, to improve a recommendation system. While typical recommender systems compare a user profile with some reference characteristics to rate unseen items, they rarely make use of the content of reviews that users have provided on a given product. In this article, we present the application of an opinion extraction system to extract opinions and suggestions from the content of the reviews, the use of the results to compare other products with the reviewed one, and eventually the recommendation of better products to the user. The recommendations are given a confidence weight by using a trust social network.